Dual-wavelength synchronously mode-locked Nd:LaGGG laser operating at 1.3 μm with a SESAM. Issue 51 (23rd June 2017) - Sun, Xiaoli; He, Jingliang; Jia, Zhitai; Ning, Jian; Zhao, Ruwei; Su, Xiancui; Wang, Yiran; Zhang, Baitao; Yang, Kejian; Zhao, Shuang
Abstract : A diode-end-pumped synchronously dual-wavelength mode-locked Nd:LaGGG laser operating at 1.3 μm with a semiconductor saturable absorber mirror was demonstrated for the first time. Abstract : We have demonstrated a diode-end-pumped synchronously dual-wavelength mode-locked Nd 3+ :(La0.1 Gd0.9 )3 Ga5 O12 (Nd:LaGGG) laser operating at 1.3 μm with a semiconductor saturable absorber mirror (SESAM) for the first time to our knowledge. The mode-locked laser emitted an average output power of 530 mW with two wavelengths centered at 1331.2 and 1336.5 nm. The pulse duration and repetition rate were 17 ps and 37.6 MHz, respectively. A frequency beat signal with respect to two stationary wave interference patterns of 0.876 THz was observed from the autocorrelation trace.